1994
DOI: 10.1073/pnas.91.13.6191
|View full text |Cite
|
Sign up to set email alerts
|

A nuclear juvenile hormone-binding protein from larvae of Manduca sexta: a putative receptor for the metamorphic action of juvenile hormone.

Abstract: A 29-kDa nuclear juvenile hormone (JH)-binding protein from the epidermis of Manduca sexta larvae was purified by using the photoaflinity analog for JH II ([3H] Juvenile hormone (JH), a sesquiterpenoid, regulates both metamorphosis and reproduction in insects (1). In the larva, JH is present throughout the growth phase, and its presence at the time of the ecdysteroid-induced molt is critical to prevent metamorphosis. The primary morphogenetic effect of JH is to guide ecdysteroid action so as to prevent its act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 27 publications
1
61
0
1
Order By: Relevance
“…Takeout is a circadian clock-regulated output gene and has been proposed as a direct molecular link between the circadian clock and the feeding/starvation response in Drosophila (SarovBlat et al, 2000). There are 20 genes of the takeout family in the fruit fly (Dauwalder et al, 2002) and proteins of this family are related to hemolymph JHBPs of Lepidoptera and to the JP29 protein initially thought to represent a JH receptor in M. sexta (Palli et al, 1994). It has been proposed that Takeout participates in a circadian output pathway that conveys temporal and food status information to feeding-relevant metabolism and activities (Sarov-Blat et al, 2000).…”
Section: Takeout/jhbp Homolog and Retinol-binding Protein Homologmentioning
confidence: 99%
“…Takeout is a circadian clock-regulated output gene and has been proposed as a direct molecular link between the circadian clock and the feeding/starvation response in Drosophila (SarovBlat et al, 2000). There are 20 genes of the takeout family in the fruit fly (Dauwalder et al, 2002) and proteins of this family are related to hemolymph JHBPs of Lepidoptera and to the JP29 protein initially thought to represent a JH receptor in M. sexta (Palli et al, 1994). It has been proposed that Takeout participates in a circadian output pathway that conveys temporal and food status information to feeding-relevant metabolism and activities (Sarov-Blat et al, 2000).…”
Section: Takeout/jhbp Homolog and Retinol-binding Protein Homologmentioning
confidence: 99%
“…Yet this rJP29 bound epoxybishomofarnesyldiazoacetate (EBDA), the photoaffinity analog of JH I, and this binding could be prevented by excess JH I or other similar hydrophobic molecules. Immunocytochemistry using a polyclonal antibody prepared against bacterially produced JP29 showed that this protein was located in the nuclei (Palli et al, 1994); however, studies reported below show that it is also present in the insecticyanin granules.…”
Section: Introductionmentioning
confidence: 91%
“…Immunodetection of JP29 was either with a monoclonal antibody (1:3000) (Charles et al, 1996) or with an affinity-purified polyclonal antiserum (Palli et al, 1994) (1:1000) followed by detection with O-dianisidine (Minnick and Spence, 1988) or the more sensitive Renaissance immunoblot chemiluminescence reagent (DuPont NEN). Immunodetection of insecticyanin was with a polyclonal antibody (1:1000) and O-dianisidine.…”
Section: Protein Extraction Sds Gel Electrophoresis and Immunoblottingmentioning
confidence: 99%
See 2 more Smart Citations